Static stretching reduces power production in gymnasts - McNeal, J. R.; Sands, W. A. (2001)
Fourteen female gymnasts, competitive levels 7-9, (149.2 ± 11.8 cm, 97.3 ± 26.4 lbs) performed drop jumps onto a timing mat under two conditions. On one day the gymnasts were stretched statically for 30 seconds on 3 different exercises (Figure 1: stair stretch, partner supine stretch, and pike stretch). These exercises were performed twice in a circuit fashion. The gymnasts then immediately performed 3 drop jumps. We evaluated the time on the ground for each gymnast, as well as the height she achieved in the jump.